A new species of rhodnius from Brazil (Hemiptera, reduviidae, triatominae) - da Rosa, João Aristeu [UNESP]; Justino, Hernany Henrique Garcia; Nascimento, Juliana Damieli; Mendonça, Vagner José; Rocha, Claudia Solano [UNESP]; de Carvalho, Danila Blanco [UNESP]; Falcone, Rossana [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP]; de Oliveira, Jader [UNESP] (Pensoft Publishers, 2017)
A colony was formed from eggs of a Rhodnius sp. female collected in Taquarussu, Mato Grosso do Sul, Brazil, and its specimens were used to describe R. taquarussuensis sp. n. This species is similar to R. neglectus, but distinct characters were observed on the head, thorax, abdomen, female external genitalia and male genitalia. Chromosomal differences between the two species were also established.
Keywords: Brazil; Cytotaxonomy; New species; Rhodnius; Taxonomy; Triatominae